Exploration of The Social Context of The Pandemic in The Andromeda Strain by Michael Crichton: A Recent Review - Ali, Muhammad Ilham (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
This study looks at how this novel depicts a society that is both fascinated by science and terrified. This study in the book "The Andromeda Strain" offers a perceptive viewpoint on pandemics and their social repercussions. This research analyzes the social conditions and circumstances during the pandemic in The Andromeda Strain. This research uses the descriptive qualitative method with the Mimetic and sociological approaches.  Based on the research findings and analysis, the result shows the existence of social changes due to the pandemic in this novel. These changes are the actions all the characters involved in the book take. These actions include cases of mass death due to a bacterium called Andromeda and cases of suicide, but there are also prevention efforts such as lockdowns and quarantines or efforts tackling bacteria; research called the wildfire project was also held, and there was also cooperation in dealing with existing cases of andromeda bacteria.Keywords: Pandemic, Social Situation, The Andromeda Strain.